Pengembangan Pelabuhan Mattoanging Dalam Mendukung Pengembangan Wilayah Sekitarnya - Dzulfadhly Djaenuddin; Murshal Manaf; Kamran Aksa (Fakultas Teknik Universitas Bosowa, 2021)
The potential of the Bantaeng district agricultural sector for rice, maize, onion, potato, cabbage, chinese cabbage and carrots has sufficient value to meet the district itself and other regions. For Jeneponto Regency, the potential of the agricultural sector which already has a value sufficient to fulfill its own district and other regions, namely corn and salt commodities. Meanwhile, for the Selayar Islands Regency, the agricultural sector does not have sufficient value to fulfill its territory but has sufficient fishery potential to fulfill its own district and other regions. The need to develop Matoanging Port by increasing the availability of facilities is due to the potential of the area, where the role of the port in this case is to become one of the entry and exit points for trade needs, and to become a means of transportation used to develop the region.